2009
DOI: 10.1080/09546630902991484
|View full text |Cite
|
Sign up to set email alerts
|

A case of imiquimod-induced alopecia

Abstract: Imiquimod cream 5% is an immune modifier approved for the treatment of genital warts, actinic keratosis, and basal cell carcinoma. This case report presents an isolated case of telogen effluvium after 6 weeks of imiquimod treatment for an actinic keratosis on the scalp. Based on this case presentation, telogen effluvium is a potential rare side effect from imiquimod treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…3 A systematic literature research found only 1 case of localized hair loss in the crown region of the scalp after topical IMQ treatment for actinic keratosis, presumably caused by a local rather than a systemic side effect. 7 We were unable to identify any other report on dermatologic or gynecologic patients with IMQ-induced hair loss. However, compared with the widespread use in dermatology, IMQ use in gynecology as an intravaginal application is still limited.…”
Section: Discussionmentioning
confidence: 97%
“…3 A systematic literature research found only 1 case of localized hair loss in the crown region of the scalp after topical IMQ treatment for actinic keratosis, presumably caused by a local rather than a systemic side effect. 7 We were unable to identify any other report on dermatologic or gynecologic patients with IMQ-induced hair loss. However, compared with the widespread use in dermatology, IMQ use in gynecology as an intravaginal application is still limited.…”
Section: Discussionmentioning
confidence: 97%
“…Based on a literature search, we identified only two articles related to localized hair loss after topical imiquimod treatment [13,14]. The first study reported the case of a patient treated for actinic keratosis on the scalp, following which telogen effluvium occurred six weeks into the treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although all cases were imiquimod induced, the routes of administration and clinical manifestations were different. One patient developed localized alopecia at the treated site after treatment with topical imiquimod for SCC in situ on the scalp [ 123 ]. In the other two cases, diffuse hair loss occurred after self-application of vaginal suppositories (containing 6.25 mg imiquimod) for the treatment of cervical intraepithelial neoplasia [ 122 ].…”
Section: Rare Imiquimod-associated Cutaneous Side Effectsmentioning
confidence: 99%